MATERIAL CATEGORIES AND THEIR CLASSIFICATIONS IN LINGUISTICS (International Educators Conference, 2025)
In Linguistics, categories of substance and their classifications are one of the important areas of linguistics. Substance, i.e. modal categories, serves to express the views, attitudes, probability, necessity, permission, and other moods of the speaker in the sense of the sentence. These categories are closely related to the semantic layer of language and also include the social, cultural and psychological aspects of speech. Substantive categories not only enrich the meaning of a sentence, but also help to fulfill the communicative functions of speech.